Soil gases, pathfinders for exploration of buried sulphide deposits: insights from laboratory experiments. Issue 1 (1st December 2019) - Plet, Chloe; Siégel, Coralie; Noble, Ryan; Anand., Ravi; Woltering, Martijn; Thorne, Robert; Pagès, Anais; Spinks, Sam
Summary: The future of mineral resources in Australia relies on the discovery of deposits under sedimentary cover. Traditional surface geochemistry techniques are of limited use in this context, and alternative exploration tools such as the detection of soil gases are gaining increasing interest. Previous studies have highlighted the potential of soil gases, such as sulphur gases and soil gas hydrocarbons, for locating buried mineralisation. Here, we performed laboratory weathering experiments of sulphides under sterile and non-sterile conditions to gain insights into the origin of these gases. The experiments revealed that hydrocarbon gases could not be detected, suggesting they commonly originate from microbial ecosystems in the cover and/or in the soil. In addition, equilibrium thermodynamic predictions indicate a larger range of sulphur gases than detected, which suggests the experimental system did not reach thermal equilibrium. Our results also reveal that CS2 is the most abundant gas produced, and could be of particular interest as a pathfinder for mineral exploration through cover.